2020
DOI: 10.1158/1538-7445.am2020-2915
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2915: Preclinical characterization of PRT543, a potent and selective inhibitor of protein arginine methyltransferase 5 (PRMT5), with broad antitumor activity in in vitro and in vivo models

Abstract: Protein arginine methyltransferase 5 (PRMT5) is the major type II PRMT that catalyzes the formation of symmetrical dimethyl arginine (SDMA) on protein substrates and plays important roles in various cellular pathways including tumorigenesis. PRMT5 can methylate histones H3 and H4, thereby leading to repression of tumor suppressor genes at specific loci. PRMT5 also regulates gene expression on a global level by methylating and altering the function of transcription factors such as p53, E2F-1, NF-κB and others. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…3C ). Exon loss and intron retention are associated with disrupted gene (e.g., by nonsense-mediated decay) and protein expression ( 37 ). Global analysis of genes with exon skipping or intron retention events following treatment of A2780 cells with C220 is represented by the violin plot in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3C ). Exon loss and intron retention are associated with disrupted gene (e.g., by nonsense-mediated decay) and protein expression ( 37 ). Global analysis of genes with exon skipping or intron retention events following treatment of A2780 cells with C220 is represented by the violin plot in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To do so, we tested the combination of PRT543 with olaparib in an ovarian cancer PDX model (CTG-0703, BRCA1 mutated). PRT543 is an orally bioavailable potent and selective PRMT5 inhibitor, which is active in human and rodent models ( 37 ). PRT543 shows improved oral pharmacokinetics in rodents, compared with C220.…”
Section: Resultsmentioning
confidence: 99%
“…Among several PRMT5 inhibitors, PRT811 was shown to be brain penetrant in preclinical studies [87], and an open-label phase 1 study in patients with advanced cancers including solid tumors, CNS lymphoma, and/or high-grade gliomas is actively recruiting (NCT04089449). Another potent PRMT5 inhibitor with preclinical activity, PRT543 [88], is actively being tested in a phase 1 study in patients with advanced solid and hematologic malignancies (NCT03886831). A preclinical study testing a potent, type I PRMT inhibitor, GSK3368715 (EPZ019997), showed cytotoxicity mostly in hematologic malignancies and in a subset of solid tumor cell lines, including 13% of pancreatic cancer [89].…”
Section: Clinical Trials Of Small-molecule Splicing Inhibitorsmentioning
confidence: 99%